ANALISIS ATAS ANNUAL REPORT YANG SUDAH TERINTEGRATED PT. BFI FINANCE INDONESIA TBK: STUDI INTERPRETIVE DALAM PRESPEKTIF SEMIOTIKA DAN RETORIKA - B2091171003, DIMAS PATRIA AKBAR WIBOWO (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2019)
The research aimed at understanding aspects of semiotics and rhetoric in integrated reporting PT BFI Finance Indonesia Tbk between 2016 and 2017. The Research used qualitative methodology employing content analysis approach. The sample of the research was state owned enterpriseÂ wich runs in finance and has more that 10 trillion assets.Â The research showed that semiotics aspects was confirmed in annual report of the company. Integrated annual report of PT BFI Finance Indonesia Tbk was made to create rhetorical story to build positive image and to get legal legitimate from stakeholders. The research has two limited result in a way that the object of the study only focused on one company, that is PT BFI Finance Indonesia Tbk, as a result the research finding was not same. If it is implemented in other company in the future, the result might be diffrent. Second, since the integrated reporting on annual report of PT BFI Finance Indonesia Tbk used semiotics interpretive paradigm, subjectivity might happen. Â Keywords: Integrating Reporting,Â Rhetoric, Semiotics.DAFTAR PUSTAKAArgonda, Antonio. (2011). â€œStakeholder Theory and Value Creationâ€.Â Â Â Â Â Â Â Â Working Paper, WP-992.Â Arnold, Carroll. C. (1982). â€œIntroduction in The Realm of Rhetoric Ch. Perelman Ed (Eds) Kulbackâ€. Notre Dame: The University of Notre Dame Press, pp.vii-xx.Â Brennan, Niamh dan Sidney J. Gray. (2000). â€œRhetorik and Argument ini Financial Reporting : disclosures in profit forecasts and takeover documentsâ€. ACCA Occasional Research Paper No 31, Certfied Accountants Educational Trust, London, ISBN 1-85908-317-X.Bogdan, Robert C. dan Biklen Kopp, (1982), Qualitative Research for Education: An Introduction to Theory and Methods. Allyn and Bacon, Inc.: Boston London.Â Budiani, Rizka Julia. (2011). â€œNarsisme dalam Pelaporan Keuangan: Analisis Semiotik atas laporan keuangan Perusahaan yang mengalami Kerugianâ€. Skripsi, Semarang: Fakultas Ekonomi Universitas Diponegoro.Camiciottoli, Belinda Crawford. (2012). â€œOral Finance Reporting: A Rhetorical Analysis of Earnings Callâ€. Skripsi, Franco Angeli, Milano, Italy: Universitasdi PisaCarter P. Dan N. Jackson. (2004) â€œFor the sake of Argument: Towardsan Understanding of Rhetoric as Processâ€. Jurnal Manajemen, 41:3, pp.469-491Chariri, Anis. (2007). â€œRhetorics in Financial Reporting: An Interpretive case Studyâ€,Â jurnal Akuntansi dan Keuangan, Vol 12, No 2, pp.53-70Chariri, A. dan Nugroho. F. A. (2009). â€œRetorika dalam Pelaporan Corporate Social Responsibility : Analisis Semiotik atas Sustainibility Reporting PT. Aneka Tambang, Tbk. SimposiumÂ C.S Peirce, (1919).Â â€œTeori segitiga makna atau triangel meaningâ€, jurnal Akuntansi dan Keuangan, Vol 15, No 34, pp 67-70Diajeng, et al. (2014). â€œNarsisme dalam pelaporan Corporate Social Responsibility: Analisis Semiotik Atas Sustainability Reporting PT. Kaltim Prima Coal dan PT. Perkebunan Nusantara XIII (Persero)â€. E-journal Ekonomi Bisnis dan Akuntansi, Volume 1, pp. 32-41.Ernst and Young. (2014). Integrated Reporting â€“ Elevating Value.Â http://www.ey.com. (diakses pada 25 Oktober 2015)Â Feldman, Martha S., and Kaj SkoÂ¨ldberg. 2002. Stories and the rhetoric of contrariety: Subtexts of organizing (change). Culture and Organization 8 (4): 275â€“92.Ferdinand de. Saussure,Â (1996). Pengantar Linguistik Umum. Yogyakarta: Gadjah Mada University Press.Financial Accounting Standards Board (FASB). 1978. â€œStatement of Financial Accounting Concepts No.1: Objectives of Financial Reporting by Business Enterprisesâ€. Stamford. Connecticut.Fitriany, Kiki. (2009) â€œRetorika Dalam Pelaporan keuangan: Analisis Narrative Text Dalam Annual Report perusahaan yang mengalami Kerugianâ€, Skripsi, Semarang : Fakultas Ekonomi Universitas Diponegoro.Fontaine, Charles. Antonie Haarman dan Stefan Schmid.(2006, Desember). â€œThe Stakeholder Theoryâ€. Research paper, Edlays Education 1.1Gentur Agustinus Naru (2008), mahasiswa Universitas Padjajaran Program Studi Ilmu Komunikasi Jurnalistik yang berjudul â€Analisis Semiotika Roland Barthes Terhadap Representasi Citra Presiden Berasal dari dimaknai menghasikan Bahasa Kata-kata Ide.Harahap, Sofyan Syafiri. (2008). Analisa Kritis atas Laporan Keuangan. Jakarta; PT. Raja Grafindo Persada.Haslinda Yusoff, Glen Lehman, (2009)